PENGOLAHAN AIR MINUM DENGAN KARBON AKTIF BUBUK Prinsip Dasar Perhitungan, Perencanaan Sistem Pembubuhan Dan Kriteria Disain - Said, Nusa Idaman (Center for Environmental Technology, 2007)
Activated carbon is substance or material which is often used in processing of drinking water to eliminate such's pollutant for example : organic matter, odors, ammonia, detergent, phenol compound, organic compound of methane derivates, and others substances, which cannot be eliminated by usual processing like coagulation, flocculation, precipitation and filtration.Ã‚Â The processing of drinking water using Powder Activated Carbon (PAC), influenced byÃ‚Â water flow rate, concentration of pollutant to be eliminated, injection rate of activated carbon, contact time as well as influenced by type of process for example single stage operation or multi stage operation either through cross current operation or with countercurrent operation. Despitefully is also influenced by nature of activated carbon it's self.Ã‚Â Processing of drinking water using powder activated carbon very compatible and economic for processing in a state of emergency for example at the time of dry season where quality of water become worse, because its can be conducted as according to existing equipments without making special equipments.Kata Kunci : Pengolahan, air minum, karbon aktif bubuk.